The CLiGS Textbox: Building and Using Collections of Literary Texts in Romance Languages Encoded in TEI XML - Christof Schöch (OpenEdition, 2019)
The CLiGS textbox is published by the Computational Literary Genre Stylistics (CLiGS) group. The textbox is the group’s publication channel for several collections of literary texts. We describe the rationale for the manner in which the collections of literary texts included in the textbox have been compiled, annotated, and published. Furthermore, we suggest several ways in which the text collections can be used for research in literary studies. We aim to document some of the work of the CLiGS group, to showcase the unique TEI XML-based collections of French, Spanish, Spanish-American, and Portuguese novels and French drama we make available, and to encourage reuse of these text collections by others. We argue that agreement on common formats and procedures for text preparation, encoding, and publication fosters the accessibility, analysis, and reuse potential of literary text collections.